Are Georgian adolescents satisfied with their body image? - MAGDA RUKHADZE (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: The purpose of this research is to learn more about how Georgian adolescents view their bodies and what factors play a role in shaping their body images.Method: Eighty Georgian secondary school teenagers were questioned for the research. A questionnaire was used to gather the data for the study. Questions about the respondent’s demographics, body image, sense of self-worth, etc., were included in the survey instrument. The information was examined utilizing SPSS 23.Findings: The study’s results confirmed that females place a premium on their physical appearance. Their thoughts appear to be in line with traditional gender roles. At 11, teenagers begin to critically examine their physical presentation. Internet users (78.8%) and television viewers (52.5%) gave similar answers regarding the greatest impact on their self-perception due to their appearance. Teens would welcome the chance to experiment with new styles. The majority of them would alter their weight, then their height, and finally, their body type. Teenagers with a healthy sense of self-worth are happier with their physical appearance than their less confident peers.Implications/Novel Contribution: The questionnaire provides a broad sketch of the respondent’s knowledge of physical form. It also discusses the importance of self-appreciation and the factors that play a role in helping adolescents’ self-esteem. Findings should be used to encourage young people to develop personally and professionally and to increase their sense of self-worth.